Subsequent measurement of non-current assets – The impact of the fair value concept choice on total comprehensive income of listed companies in the Republic of Serbia - Aleksandra Arsenijević; Dejan Spasić (Anali Ekonomskog fakulteta u Subotici, 2023)
In response to investor demands, with the introduction of the fair value (FV) concept, other comprehensive income (OCI) has become a significant indicator of changes in the current values of certain financial statement items in successive periods. Although it deviates from the traditional concept of historical cost (HC) and its prudence principle, on which reliability rests, the use of fair value contributes to the relevance of the presented information. The total comprehensive income (TCI), as a summary of realized and unrealized gains and losses recognized in the income statement, i.e. OCI, represents a valuable base of relevant information for investors and other users of financial statements.The paper focuses on a sample of listed entities on the Regulated Capital Market of Serbia for the period 2016-2020 and finds that the FV concept is predominantly used for the subsequent measurement of property, plant and equipment (PP&E). In addition, we analyze the impact of changes in the fair value of certain non-current assets’ items (i.e.: PP&E, intangible assets and long-term investments) on TCI. Our research shows that some OCI items have a divergent impact on TCI, and, thus, different information power, which can increase uncertainty, i.e. make it harder for analysts to predict net income.